Uncertain Altruism and Non-Linear Long-Term Care Policies - Chiara Canta; Helmuth Cremer (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study the design of public long-term care (LTC) insurance when the altruism of informal caregivers is uncertain. We consider non-linear policies where the LTC benefit depends on the level of informal care, which is assumed to be observable while children's altruism is not. The traditional topping up and opting out policies are special cases of ours. Both total and informal care should increase with the children's level of altruism. This obtains under full and asymmetric information. Social LTC, on the other hand, may be non-monotonic. Under asymmetric information, social LTC is lower than its full information level for the lowest level of altruism, while it is distorted upward for the higher level of altruism. This is explained by the need to provide incentives to high-altruism children. The implementing contract is always such that social care increases with formal care.
Keywords: H20; H50; 330; long term care; uncertain altruism; private insurance; public insurance; topping up; opting out